TINGKAT MOTIVASI PETANI DALAM KEBERLANJUTAN USAHATANI BUAH NAGA DI DESA LAMONG JAYA KECAMATAN LAEYA KABUPATEN KONAWE SELATAN - Siti Komariah; Hartina Batoa; Yoenita Jayadisastra (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This research aims 1) To determine the level of motivation of dragon fruit farmers in Lamong Jaya Village, Laeya District, South Konawe Regency 2) To determine the social sustainability of dragon fruit farming in Lamong Jaya Village, Laeya District, South Konawe Regency 3) To determine the relationship between the level of farmer motivation and sustainability dragon fruit farming in Lamong Jaya Village, Laeya District, South Konawe Regency. This research was carried out in Lamong Jaya Village, Laeya District, South Konawe Regency from April to May 2024. Determining the research location was carried out purposively with the following considerations: Lamong Jaya Village is one of the villages where the majority of the people are farmers and the majority of farmers cultivate dragon fruit. . Dragon fruit is a commodity that provides huge benefits for the people of Lamong Jaya Village. The data used in this research is quantitative data to determine the level of motivation and sustainability of dragon fruit farming in Lamong Jaya Village, Laeya District, South Konawe Regency. The results of this research show that the level of motivation of dragon fruit farmers in Lamong Jaya Village is relatively high. Meanwhile, the sustainability of dragon fruit cultivation in Lamong Jaya Village is relatively high. The level of farmer motivation and the sustainability of dragon fruit farming in Lamong Jaya Village has a significant positive relationship but the coefficient is not strong.